Habitos alimentarios actividad fisica y estado nutricional en alumnos de la facultad de enfermería de la Universidad Nacional de Trujillo Abril a Junio 2010 - Córdova Rodríguez, Laura Julie (2010)
This descriptive correlational study was conducted among students of the Faculty of Nursing, National University of Trujillo during the months of April to June 2010 with the purpose of determining the relationship between eating habits and physical activity nutritional status of students. The sample consisted of 106 students who attended the various courses of study. The instrument was a questionnaire - survey which includes questions regarding physical activity and eating habits developed by the authors taking into account the size under study and the proposed theoretical framework. The results were tabulated and presented in graphs and tables in a double-entry, numerically and percentage. The statistical analysis was applied to test independence of criteria (X2) Chi square, to measure the degree of association. According to the results, 68.9% had a normal nutritional status, 23.6% are overweight and 7.5% obese, and students with limited physical activity account for 81.1%, 17% have an adequate level of physical activity and only 1.9% are physically inactive, 77.4% have regular feeding habits, 17.9% of their habits are good and only 4.7% have bad habits. The study confirms the influence of physical activity level of the students on their nutritional status, with a value chi-square = 28,578 with a probability of 0.00 still is highly significant, ie a relation between the variables. On the other hand, to relate the type of eating habits with nutritional status of students, has a chi-square value = 6186 0186 with a probability of this being not significant, there is no relationship between variables.